Altered Cutaneous Nerve Regeneration in a Simian Immunodeficiency Virus/Macaque Intracutaneous Axotomy Model - Ebenezer, Gigi J. (2009)
To characterize the regenerative pattern of cutaneous nerves in SIV-infected and uninfected macaques, excisional axotomies were performed in non-glabrous skin at 14-day intervals. Samples were examined after immunostaining for the pan-axonal marker PGP 9.5 and the Schwann cell marker p75 nerve growth factor receptor. Collateral sprouting of axons from adjacent uninjured superficial dermal nerve bundles was the initial response to axotomy. Both horizontal collateral sprouts and dense vertical regeneration of axons from the deeper dermis led to complete, rapid reinnervation of the epidermis at the axotomy site. In contrast to the slower, incomplete reinnervation previously noted in humans after this technique, in both SIV-infected and uninfected macaques, epidermal reinnervation was rapid and completed by 56 days post-axotomy. p75 was densely expressed on the Schwann cells of uninjured nerve bundles along the excision line and on epidermal Schwann cell processes. In both SIV-infected and uninfected macaques, Schwann cell process density was highest at the earliest time points post-axotomy and then declined at a similar rate. However, SIV-infection delayed epidermal nerve fiber regeneration and remodeling of new sprouts at every time point post-axotomy, and SIV-infected animals consistently had lower mean epidermal Schwann cell densities suggesting that Schwann cell guidance and support of epidermal nerve fiber regeneration may account for altered nerve regeneration. The relatively rapid regeneration time and the completeness of epidermal reinnervation in this macaque model provides a useful platform for assessing the efficacy of neurotrophic or regenerative drugs for sensory neuropathies including those caused by HIV, diabetes mellitus, medications, and toxins.